2002
DOI: 10.1017/s014271640200005x
|View full text |Cite
|
Sign up to set email alerts
|

Reading-related skills of kindergartners from diverse linguistic backgrounds

Abstract: This study examined whether measures used to identify children at risk for reading failure are appropriate for children from different language backgrounds. Tasks assessing literacy and phonological and language processing at the beginning and end of kindergarten were administered to 540 native English speakers (NS), 59 bilingual children (BL), and 60 children whose initial exposure to English was when they began school (ESL). Although the BL and ESL children performed more poorly than the NS children on most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 57 publications
(53 reference statements)
9
57
0
2
Order By: Relevance
“…Children who performed well in Spanish performed well in English; children who performed more poorly in Spanish did so in English as well. In a similar study conducted with kindergarteners, Chiappe, Siegel, and Gottardo (2002) found that alphabetic knowledge and phonological processing abilities were the most important contributors to skilled early reading. These researchers found that neither bilingual children nor children learning English as a second language performed as well as native English speakers at the beginning of kindergarten on tasks assessing literacy and phonological and language processing, but that basic literacy skills developed in the same way across the three groups.…”
Section: Research On Inside-out Factors With Bilingual Childrenmentioning
confidence: 90%
“…Children who performed well in Spanish performed well in English; children who performed more poorly in Spanish did so in English as well. In a similar study conducted with kindergarteners, Chiappe, Siegel, and Gottardo (2002) found that alphabetic knowledge and phonological processing abilities were the most important contributors to skilled early reading. These researchers found that neither bilingual children nor children learning English as a second language performed as well as native English speakers at the beginning of kindergarten on tasks assessing literacy and phonological and language processing, but that basic literacy skills developed in the same way across the three groups.…”
Section: Research On Inside-out Factors With Bilingual Childrenmentioning
confidence: 90%
“…After decades of inquiry, researchers have a strong understanding of the skills underlying decoding (Conners, Atwell, Rosenquist, & Sligh, 2001;Seymour & Evans, 1994) and of the ways to enhance decoding skills in native speakers and L2 learners (Allinder, Dunse, Brunken, & Obermiller-Krolikowski, 2001;McCandliss, Beck, Sandak, & Perfetti, 2003;Meyer & Felton, 1999). Although some English L2 learners might initially struggle with the acquisition of decoding skills, good instruction allows English L2 learners to perform at the same levels as their native English-speaking peers on decoding after a few years of explicit instruction (Chiappe, Siegel, & Gottardo, 2002;D'Anguilli, Siegel, & Maggi, 2004;Gersten & Baker, 2000;Geva, Yaghoub-Zadeh, & Schuster, 2000). However, English L2 learners continue to perform at lower levels on reading comprehension and on the language variables that are related to listening comprehension such as vocabulary and syntactic knowledge Geva et al, 2000).…”
Section: Why Listening Comprehension?mentioning
confidence: 99%
“…From a comparative perspective, the study of Chiappe, Gottardo, and Siegel (2002) aimed to identify kindergarten children at risk for reading failure at the end of grade 1 from different language backgrounds. The authors observed that the acquisition of basic literacy skills for children with different language backgrounds developed in a similar manner.…”
Section: Introductionmentioning
confidence: 99%